ASME-JSME-KSME 2011 Joint Fluids Engineering Conference: Volume 1, Symposia – Parts A, B, C, and D 2011
DOI: 10.1115/ajk2011-05020
|View full text |Cite
|
Sign up to set email alerts
|

Toward Optimum Configuration of Circumferential Groove Casing Treatment in Transonic Compressor Rotors

Abstract: The current paper first reviews experimental and numerical investigations to understand flow physics and to develop optimum configurations of circumferential grooves in compressor rotors. Circumferential grooves are used mainly to increase stall margin in axial compressors with small decrease in aerodynamic efficiency. Although circumferential groove casing treatment has been used widely, flow mechanisms of the circumferential grooves at near stall conditions are not well understood yet. Detailed time-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…11 Among the various casing treatments, the circumferential groove casing treatment is simple in structure and has less negative effect on the efficiency of compressors. 12,13 Many investigations have been carried out to reveal the flow mechanisms for stall margin improvement by circumferential groove casing treatments. Prince et al 14 identified several effects of circumferential grooves on compressors.…”
Section: Introductionmentioning
confidence: 99%
“…11 Among the various casing treatments, the circumferential groove casing treatment is simple in structure and has less negative effect on the efficiency of compressors. 12,13 Many investigations have been carried out to reveal the flow mechanisms for stall margin improvement by circumferential groove casing treatments. Prince et al 14 identified several effects of circumferential grooves on compressors.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Among the widely investigated casing treatment geometries, circumferential groove casing treatment is simple in structure, and can extend the stall margin with relatively small efficiency penalty. [8][9][10] However, the fundamental working mechanisms of circumferential casing grooves on the performance of compressors are still not well understood. The universal design criterion of circumferential casing grooves has not been established yet.…”
Section: Introductionmentioning
confidence: 99%